The role of social media marketing on e-commerce implementation and SMEs performance in Ibadan City Nigeria - Ayokunmi, Lawal Abideen (2022)
Small and medium-scale enterprises (SMEs) are known as the fabricators and stimulants of economic growth and national development for developed and developing countries, including Nigeria. This research study was inspired by the poor performance of SMEs in Nigeria, which has resulted in a severe decline in the contributions of SMEs to employment creation, gross domestic product, and export earnings for the country, especially in Ibadan city. However, SMEs’ involvement in social media marketing offers many benefits for their businesses, including enhanced brand value, sales growth, and effective social e-commerce. Thus, this research study investigated the relationship between e-commerce implementation and SME performance in Ibadan as well as the significant role of social media marketing on e-commerce implementation and SME performance. The study adopted quantitative research by using questionnaires as the main research instrument. The sample for this study comprises SMEs that registered with the SMEDAN in Ibadan city, of which 370 of them were selected as the sample size for the study. Then, the Statistical Package for Social Science (SPSS) was used to answer all the objectives of the study, and also, Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to test the relationships between variables, which served as the method of data analysis. This study found that e-commerce implementation has a positive and significant relationship with SMEs performance, whereas social media marketing has a negative but minimally significant moderating effect on the relationship between e-commerce implementation and SMEs performance in Ibadan city. The study could provide success both locally and globally, considering such a dominant advantage through social media marketing. SMEs offering social commerce were able to improve their revenue, focus on new customers, and control their costs to meet the expected pricing and customer needs.